Enzymatic processes in oil bioremediation and phytoremediation in mangrove sediments: a review (Research, Society and Development, 2021)
Several oil spills in seas and oceans have occurred in recent decades, mainly affecting estuaries and mangroves. Environmental accidents involving petroleum, its derivatives and the waste generated have been a growing concern, as petroleum hydrocarbons are considered toxic organic contaminants that are difficult to degrade. Biotechnological advances have led researchers to adopt bioremediation and phytoremediation as potentially effective alternatives for contaminated soils and sediments, and the use of enzymes has been adopted as a strategy beyond the use of plants and microorganisms in bioremediation. This study consists of a literature review based on books, articles, theses, dissertations and websites, in order to gather and evaluate enzymatic processes in phytoremediation and phytoremediation in environments impacted by petroleum activities.